Acupuncture combined with Tongxieyaofang for diarrhea-type irritable bowel syndrome: A protocol for meta-analysis. Issue 48 (25th November 2020) - Li, Yi-Lin; Yao, Cheng-Jiao; Lei, Rong; Xie, Fengjiao; Xiong, Qin; Luo, Li-Hong; Feng, Pei-Min
Abstract: Background: As a traditional Chinese medicine external treatment method, acupuncture is characterized by simple operation, significant treatment effect and few side effects. Tong-Xie-Yao-Fang (TXYF), a Chinese patent medicine, combined with acupuncture has been widely used on treating Diarrhea Predominant Irritable Bowel Syndrome (IBS-D). However, the efficacy and safety of TXYF combined with acupuncture for the treatment of IBS-D are unclear. This study aims to investigate verify the efficacy and safety of TXYF combined with acupuncture for IBS-D. Methods and analysis: Randomized controlled trials of TXYF combined with acupuncture for all IBS-D will be searched in PubMed, the Cochrane Library, Embase, Web of Science, the China National Knowledge Infrastructure, Wanfang Database, Chinese Science and Technology Periodical Database, and Chinese Biomedical Literature Database from inception to October 20, 2020. And Baidu Scholar, Google Scholar, International Clinical Trials Registry Platform, and Chinese Clinical Trials Registry will be searched to obtain more relevant studies comprehensively. The methodological qualities, including the risk of bias, will be evaluated using the Cochrane risk of bias assessment tool, while confidence in the cumulative evidence will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Two researchers will perform data extraction and risk of bias assessment independently. Statistical analysis will be conducted in RevMan 5.3. Results: Based on the current evidence, the potential rank of the efficacy and safety of TXYF plus acupuncture for IBS-D will be assessed. Conclusion: The findings of the study will provide helpful evidence for the efficacy and safety of TXYF combined with acupuncture in the treatment of IBS-D, facilitating clinical practice and further scientific studies.